Prevalence of Group B Streptococcus Vaginal Colonization in The Third Trimester of Pregnancy. - MR Nazer; E Rafiei Alavi; E Nazer; M Khamechi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2011)
Introduction: Group B Strepococcus(GBS) is one of the most important causes of neonatal infections including septicemia and meningitis. It also plays an important role in maternal infections such as chorioamnionitis, pyelonephritis, metritis and post partum infection. The present study was carried out to find the prevalence of GBS in pregnant women with 28 to 38 weeks gestational age. Methods: In this study, 100 pregnant women referring to the obstetrical clinic of Asalian Hospital in Khorramabad city in the third trimester of pregnancy (after explaining the study, getting informed consent and demographic informations) were tested for GBS by taking a vaginal sample. The sample was taken by sterile cotton swab. The swabs were placed in transport media, transported to the central Lab, and were inoculated in blood agar. Then all samples were analyzed for the presence of GBS. Results: In this study, the prevalence of positive vaginal GBS culture in pregnant women was 14% (CI: 7.2-20.8%). No significant correlation were found between this positive culture and maternal age, gestational age, abortion status, diabetes mellitus and pregnancy induced hypertension, while a significant correlation was found between positive cultures and parity. Conclusion: As the colonization rate of GBS in pregnant women of Khorramabad is high, routine culture-based screening is recommended for all pregnant women in third trimester of pregnancy.